Pengaruh Desain Produk, Pengetahuan Produk, Dan Kesadaran Merek Terhadap Minat Beli Produk Eiger - Irvanto, Ogy; Sujana, Sujana (Jurnal Ilmiah Manajemen Kesatuan, 2020)
Trading competition between companies is getting tighter, as consumers' needs for products increase. Consumers can now choose the brand of products they need. In the increasingly fierce competition in the business world, in line with the increasingly dynamic desires and needs of consumers. The purpose of this study is (1) to determine the effect of product design on consumer buying interest in Eiger products. (2) to determine the effect of product knowledge on consumer buying interest in eiger products. (3) to determine the effect of brand awareness on consumer buying interest in eiger products. (4) to determine the effect of product design, product knowledge, and brand awareness together on consumer buying interest in eiger products. The number of respondents in this study amounted to 250 respondents drawn from the people of Bogor City. This research uses quantitative methods, and data collection is done by distributing questionnaires online. Sampling using non-probability sampling method with purposive sampling technique. With analytical techniques using the Structural Equation Model (SEM) which is processed using the AMOS 25 program. The results obtained in this study are product design influential and significant to buying interest, product knowledge has an effect on and significant on buying interest, product knowledge has an effect on and has significant influence on buying interest . Keywords: Product Design, Product Knowledge, Brand Awareness and Purchase Interest